Penentuan Aktivitas Antioksidan, Kandungan Fenolik Total, dan Uji Sitotoksik dari Ekstrak Rumput Banto (Leersia hexandra Swartz.) - Emil Salim; Suryati; Rifi Iron Akhfifni (Jurnal Kimia Unand, 2022)
Banto grass, known as animal feed and tradicional medicine, has anticancer, antioxidant, and antihypertensive effect. The purpose of this study was to determine the secondary metabolite content, antioxidant activity, total phenolic content and cytotoxic activity. Maceration extraction with variation of solvent (hexane, ethyl acetate, and methanol) was used to obtain the banto grass extract. Antioxidant activity of the banto grass and control determined using 1,1-Diphenyl-2-picrylhydrazil (DPPH) method: Methanol (IC50 154,75 mg/L), Ethyl Acetate (IC50 224,47 mg/L) and Hexane (IC50 268,59 mg/L). Vitamin C (IC50 9,31 mg/L) served as control.The methanol extract had weak antioxidant activity while ethyl acetate and hexane extract had very weak antioxidant activity. The banto grass was screened for total phenolic content using Folin-Ciocalteu method: Methanol (0,3 mg GAE/g dry extract), Ethyl Acetate (0,23 mg GAE/g dry extract), and Hexane (0,11 mg GAE/g dry extract). There was negative correlation between IC50 and total phenolic content of the banto grass extract. Cytotoxic activity of the banto grass determined using Brine Shrimp Lethality Test (BSLT) method: Methanol (LC50 2454, 14 mg/L), Ethyl Acetate (LC50 233,13 mg/L) and Hexane (LC50 220,39 mg/L). The hexane and ethyl acetate extract had toxic properties while methanol extract had not toxic properties.